Pengaruh Servant Leadership, Kompetensi, dan OCB terhadap Kinerja Guru SD di Gandus - Nabella Aulia Sari; Dessy Wardiah; Andi Rahman (Lembaga Pengembangan Kinerja Dosen, 2025)
The aim of this research is to determine and analyze: 1) The influence of the principal's Servant Leadership on the Performance of Public Elementary School Teachers in Gandus District. 2) The influence of teacher competency on state elementary school teachers in Gandus District. 3) The Influence of Citizenship Behavior on the Performance of Public Elementary School Teachers in Gandus District. And 4) The simultaneous influence of the Principal's Servant Leadership, Teacher Competency and Citizenship Behavior on the Performance of Public Elementary School Teachers in Gandus District, Palembang City. This research uses quantitative methods with a correlational approach. The research sample consisted of 122 teachers from state elementary schools in Gandus District. Data collection techniques use questionnaires and documentation. Data analysis was carried out using multiple linear regression using the SPSS version 26 application. The results of the research showed that there was a positive and significant influence both partially and simultaneously between the Principal's Servant Leadership, Teacher Competence and Citizenship Behavior on Teacher Performance. The magnitude of the influence of these three independent variables on teacher performance simultaneously is 78.9%, while the remaining 21.1% is influenced by other variables not examined in this research.